Engineering fundamentals an introduction to engineering - Moaveni, Saeed (Brooks/Cole-Thomson Learning, 2002)
This book introduces students to basic study skills while also introducing the engineering discipline in the early chapters. Having thoroughly prepared students, the author then introduces basic principles, physical laws, engineering materials, computer tools, and engineering standards and codes at a basic level so students comprehend the importance of these topics.